Factors Affecting Satisfaction on the Quality of Tourism Services at Flamingo Dai Lai Resort - Thi Mai Huong, Nguyen; Quyen, Bui Thi (VNU JOURNAL OF ECONOMICS AND BUSINESS; Vol 37 No 1, 2021)
Determining the degree of influence of factors on tourism service quality is a useful tool for managers in strategic planning, planning tourism development. This study uses a questionnaire designed from the results of previous studies, surveying 117 customers who have stayed at Flamingo Dai Lai Resort to find out factors that affect the satisfaction of customers to the quality of tourism services of this resort. Regression analysis results show that there are 3 factors affecting the satisfaction of customers who have used the service here: Weather, climate, environment (Ecological environment); Staff behavior; Quality of infrastructure. The remaining factors are not enough to conclude a linear relationship with the satisfaction of customers who have come to this resort.